Differences in Adjustment between Individuals with Alpha-1 Antitrypsin Deficiency (AATD)-Associated COPD and Non-AATD COPD. (21st March 2013) - Holm, Kristen E.; Borson, Soo; Sandhaus, Robert A.; Ford, Dee W.; Strange, Charlie; Bowler, Russell P.; Make, Barry J.; Wamboldt, Frederick S.
Abstract Smokers who have severe alpha-1 antitrypsin deficiency (AATD) are at risk for developing COPD earlier in life than smokers without AATD, and are likely to experience challenges adjusting to their illness because they are in a highly productive life stage when they are diagnosed with COPD. This study examined whether individuals with AATD-associated COPD differ from individuals with non-AATD COPD with regard to depression, anxiety, dyspnea, and health-related quality of life (HRQL). Cross-sectional data were collected via self-report questionnaires completed by 480 individuals with non-AATD COPD and 578 individuals with AATD-associated COPD under protocols with IRB approval. Multiple linear regression models were used to test whether individuals with non-AATD COPD differed from individuals with AATD-associated COPD with regard to depression, anxiety, dyspnea, and HRQL. All models adjusted for demographic and health characteristics. Individuals with AATD-associated COPD did not report more symptoms of depression or anxiety; however, they did report more dyspnea (B = 0.31, 95% CI = 0.16 to 0.47, p < 0.001) and impairment in HRQL (B = 4.75, 95% CI = 2.10 to 7.41, p < 0.001) than other individuals with COPD. Individuals with AATD-associated COPD were more likely to be a member of a couple (rather than single) and had a higher level of education when compared to individuals with non-AATD COPD. Resources available to persons with AATD-associated COPD, such as being in a serious relationship and having higher education, may offset the effect of age when considering symptoms of depression and anxiety in patients with COPD.